Pengaruh Mediasi Kepercayaan Belanja Online Terhadap Persepsi Resiko - iwan, gede (Jurnal Ilmiah Manajemen & Bisnis, 2016)
Purpose - The purpose of this research is to examine the effect of Trustworthiness of Internet Vendor and External Environment along with the moderating effect of Trust in Internet Shopping on Perceived Risk. Design/methodology/approach - There were two studies performed in this research. Studi 1 validated the self regulating processes; Study 2 tested the moderating effects of Trust in Online Shopping on Perceived Risk. The study of population are 165 respondent from undiknas students. Respondents were selected based on the technique of convenience sample of students who are familiarized to online shopping. The data is processed and analyzed using SEM with statistical software AMOS. Finding - The study demonstrated that Trustworthiness of Internet Vendor and the external environment has a negative and significant effect on the perceived risk of online shopping. Along with the mediating effect of Trust in Online Shopping, the external environment has a stronger effect than the variable Trustworthiness of Internet Vendor on the perceived risk of online shopping. Research limitations/implications - We found that there are emotional and rational routes influencing Trust in Internet Shopping in the online shopping process. This will contribute to other research that clarifies the influencing process of Perceived Risk in online shoppers’ motivation and behaviour. Practical implications - In the pre-purchase stage, online retailers should focus on attracting consumers by the quality of Trustworthiness of Internet Vendor. In the purchase stage, online retailers should address the emotional factors, such as Trust in Internet Shopping. In the post-purchase stage, rational factors – such as and External Environment play important roles because they can strengthen the relationship between Trust in Internet Shopping and Perceived Risk. Originality/value - This study viewed the purchase process as a different stage as consumers may make a choice at each of the purchase stages. Moreover this study found a way to examine the relationship between Trustworthiness of Internet Vendor and External Environment by exploring the moderating effects of Trust in online Shopping.